Expert consensus on diagnosis, treatment and fertility management of young breast cancer patients - Committee of Diagnosis, Treatment, and Fertility Management of Chinese Young Breast Cancer Patients (Elsevier, 2021)
Breast cancer in young females is a relatively common disease in China. Young breast cancer has aggressive clinical and pathological features. During the treatment of young females with breast cancer, issues involving the choice of surgical methods, early amenorrhea, and fertility protection may have physical, psychological, and social impacts. Thus, a multidisciplinary model of diagnosis and treatment is indispensable. The breast cancer expert committee of the National Cancer Quality Control Center organized experts in related fields in China to compile this consensus as to provide scientific and feasible solutions for rational diagnosis, treatment, and fertility management for young females with breast cancer. This consensus is based on the literature data, the views of relevant international guidelines, and the clinical practice experience of experts in different fields.